2018
DOI: 10.1007/s11121-018-0915-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Urban Neighborhood Environment on Marijuana Trajectories During Emerging Adulthood

Abstract: Although there is little difference in rates of marijuana use between White and Black youth, Blacks have significantly higher rates of marijuana use and disorder in young adulthood. Theory suggests that factors tied to social disadvantage may explain this disparity, and neighborhood setting may be a key exposure. This study sought to identify trajectories of marijuana use in an urban sample during emerging adulthood, neighborhood contexts that predict these trajectories and social role transitions or "turning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…They found that the associations were often reciprocal and more salient in some developmental periods but not in others. Reboussin et al (2019) used data from a Baltimore-based cohort study and showed that residence in neighborhoods characterized by social disorder (e.g., violence, incivilities) was associated with problematic use of marijuana in emerging adulthood, and also that living further away from alcohol outlets was protective. These studies underscore the importance of developing intervention strategies that focus on risk comprehensively, i.e., across the ecological domains in which the lives of youth are embedded, with close attention to timing of risk and developmental transitions.…”
Section: Predictors Of Marijuana Use From Multiple Ecological Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the associations were often reciprocal and more salient in some developmental periods but not in others. Reboussin et al (2019) used data from a Baltimore-based cohort study and showed that residence in neighborhoods characterized by social disorder (e.g., violence, incivilities) was associated with problematic use of marijuana in emerging adulthood, and also that living further away from alcohol outlets was protective. These studies underscore the importance of developing intervention strategies that focus on risk comprehensively, i.e., across the ecological domains in which the lives of youth are embedded, with close attention to timing of risk and developmental transitions.…”
Section: Predictors Of Marijuana Use From Multiple Ecological Domainsmentioning
confidence: 99%
“…There are few state-or nationally-representative datasets that allow for longitudinal assessments of marijuana use among adolescents, which limits opportunities to examine developmental changes in the midst of a dynamic legal and normative environment for marijuana use. The longitudinal studies in this special issue are geographically-limited; for example, Reboussin et al (2019) used data from a cohort of 18-21-year-olds based in one city. Add Health is a national longitudinal study that has been used extensively to study etiology of heath and health risk behaviors among US youth (see Nguyen et al 2019), but it is not well suited for research aiming to examine recent marijuana policy changes.…”
Section: Longitudinal Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are particularly salient in impoverished urban neighborhoods where residents may be unable to monitor activities in their neighborhoods and, as a result, drug use (both licit and illicit) may flourish promoting ease of availability as well as reinforcement of positive drug-using norms (Sampson et al, 1997). These neighborhoods also often lack the social capital to provide positive experiences for youth which can result in the formation of deviant peer groups where values conducive to drug use can arise and spread (Dishion et al, 1999;Patterson et al, 1992). In addition, early use of alcohol and tobacco may provide a surrogate both for availability of drugs and exposure to positive drug -taking norms, as well as a possible 'common liability' to use other drugs and may, thus, be important to consider in relation to cannabis use trajectories, as well as opioid misuse (Degenhardt et al, 2009;Palmer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Community disadvantage as assessed via census data has been extensively used in the literature, with higher levels of disadvantage significantly associated with increased marijuana use offers and heavy marijuana use (Reboussin et al, 2015). In addition, higher levels of community disadvantage have been associated with a greater concentration of alcohol outlets (e.g., Furr Holden et al, 2018;Milam et al, 2014), which have been linked to higher levels of violent crime, decreased life expectancy, and increased substance use (Furr-Holden et al, 2018;Jennings et al, 2013;Reboussin et al, 2018). Using ArcMap, a spatial join (appends data from two map layers using geographic location) was conducted to determine the census tract for each participant.…”
Section: Community Disadvantagementioning
confidence: 99%